Genetically engineered mesenchymal stem cells with dopamine synthesis for Parkinson’s disease in animal models - Jun Li; Nan Li; Jingkuan Wei; Chun Feng; Yanying Chen; Tingwei Chen; Zongyong Ai; Xiaoqing Zhu; Weizhi Ji; Tianqing Li (npj Parkinson's Disease, 2022)
Abstract Although striatal delivery of three critical genes for dopamine synthesis by viruses is a potential clinical approach for treating Parkinson’s disease (PD), the approach makes it difficult to finely control dopamine secretion amounts and brings safety concerns. Here, we generate genetically engineered mesenchymal stem cells encoding three critical genes for dopamine synthesis (DOPA-MSCs). DOPA-MSCs retain their MSC identity and stable ability to secrete dopamine during passaging. Following transplantation, DOPA-MSCs reinstate striatal dopamine levels and correct motor function in PD rats. Importantly, after grafting into the caudate and putamen, DOPA-MSCs provide homotopic reconstruction of midbrain dopamine pathways by restoring striatal dopamine levels, and safely and long-term (up to 51 months) correct motor disorders and nonmotor deficits in acute and chronic PD rhesus monkey models of PD even with advanced PD symptoms. The long-term benefits and safety results support the idea that the development of dopamine-synthesized engineered cell transplantation is an important strategy for treating PD.